Keragaman genetik puyuh Jepang (Coturnix japonica) berdasarkan analisis sekuen DNA mitokondria gen Cytochrome-b - Novisa Adimaka; Muhammad Rifki; Ratih Dewanti; Muhammad Cahyadi (Faculty of Animal Science, Universitas Brawijaya, 2019)
Coturnix japonica is a Japanese quail which is commonly raised in Indonesia. The aim of the study was to determine the genetic diversity of Japanese quail (Coturnix japonica) based on complete sequence of mitochondrial DNA Cytochrome b gene analysis. This study used 12 samples of quail blood collected from two different village breeding centres (VBC) representing black and brown plumage lines. Total DNA genome was isolated from whole blood by following the Wizard® Genomic DNA Purification Kit protocol (Promega, USA). The DNA amplification process in this study was carried out using novel forward and reverse primers using Primer3 software. Additionally, PCR products were sequenced and analysed using MEGA 6.0 and DNAsp v.5 softwares. A total of 21 sequences consists of 12 sequences of quail sample and 9 reference sequences obtained from NCBI website were analyzed to construct phylogenetic tree and to evaluate genetic diversity of Japanese quails. The sequence analysis showed that Japanese quail population in this study had kinship with Francolinus pintadeanus and Coturnix chinensis with an 81% bootstrap value. The genetic distance among Japanese quails was ranged from 0.000 to 0.003. In addition, the mean of genetic distance for Japanese quail was 0.002 and the mean of genetic distance for 21 samples was 0.067. Tajima D'test values were -1.35536 for Japanese quail population and -1.38090 for whole population used in this study. The conclusion of this study was the Japanese quail had low genetic diversity based on complete sequence of Mitochondrial DNA Cytochrome b gene analysis that mean Japanese quail had low level of evolution